USE OF ARTIFICIAL INTELLIGENCE TO PROTECT - Prof. G.N.Chavan; Pratiksha Nangre, Priyanka Chavan, Vinay More, Amirsohel Choudhary, Sourabh Patil (International Journal of Innovations in Engineering Research and Technology, 2022)
In recent years, artificial intelligence application have found a wide range of application for solving small and large scale civil engineering problems such as design optimization , parameter estimations and identification and damage detection. . The programming of the soil moisture sensor is done and the setup can find time duration and early detection of landslide.the detection of structural failure with the development of an integrated system using Arduino as well as soil moisture sensors. A foundation is a structural element that provides support for various loads acting on the superstructure.Soil moisture sensor,Accelero-gyro slope sensor,Humidity Sensor, Arduino,Undermining Safe SupportThis sensor used in this project. Terzhaghi equation used in vane shear test and direct shear test is used to predict these parameter quickly.vane shear test measure of shear strength of cohesive soils is useful for soils of low shear strength.